Change in business scenario during Covid 19 pandemic - Anupama, (Gyan Management Journal, 2021)
Entrepreneurship development is the means of enhancing the knowledge and skill of entrepreneurs through several classroom coaching and programs, and training. The main point of the development process is to strengthen and increase the number of entrepreneurs. It encourages them to make better judgments and take a sensible decision for all business activities. The year 2020 has witnessed a drastic change in each and every sphere of life which includes business sector also. According to World Health Organization (WHO, 2019) there are several pandemics in the history that has changed the human life. COVID-19 has initiated on 12 Dec 2019 in Wuhan city of China, and it was noticed that people are infected by pneumonia by illusory link to a shop that retails fresh sea food to people. Within week millions of people infected with this virus in China. Furthermore, at the present time 205 countries are infected with this virus and their economies.The coronavirus pandemic has gained massive scale with more than three million cases across the world. The global economy has witnessed a major downfall in business sector due to this pandemic situation. Several countries have imposed stringent measures to contain the transmission of the virus among the masses. India imposed a nationwide lockdown on March 24, which was subsequently extended till May 17.Coronavirus drastically changed the global trends. As the country enters the extended lockdown period with only essential goods being available, businesses have requested employees to work from home, and some have been shut down temporarily. A rapid change has occurred in every business. It has changed the behaviour of human, nature of trading, business and even the way of life. The main aim of my study is to find out various aspects of entrepreneurship development and entrepreneurial scenario during Covid 19.
Keywords: Teacher Effectiveness; Quality of Teaching; Covid-19 Pandemic; Teachers; Lockdown; Online Teaching; Physical Classroom; Virtual Classroom